THE URGENCY OF SHARIA FINTECH IN SOLVING CREATING A DIGITAL-BASED MANDIRI VILLAGE IN MUARA HARAPAN VILLAGE: Directly Influce and Indirectly iInflunce - Qonita, Qonita; Adrian Muhari, Muhammad Dheo; Supriyanto, Achmad Sani; Suprayitno, Eko (I-Economics, 2023)
Southern Sumatra consists of the provinces of South Sumatra, Lampung, Jambi, Bengkulu, and the Bangka-Belitung Islands. These five provinces have the fastest recovering economic growth compared to other regions in Indonesia and the highest economic growth recovery in Sumatra from 2020-2021. Therefore, this study aims to analyze what factors influence economic growth in 60 cities/districts in Southern Sumatra.